Higher efficacy of oral etoposide for mobilization of peripheral blood stem cells in patients with multiple myeloma. Issue 2 (23rd April 2022) - Qiang, Wanting; Jiang, Hua; Guo, Pei; Lu, Jing; Liu, Jin; Li, Lu; He, Haiyan; Hu, Xiaoxia; Fu, Weijun; Du, Juan
Abstract : Abstract: This study compares the efficacy, toxicity, hematopoietic recovery, and cost of stem-cell mobilization using intermediate-dose cyclophosphamide (IDCy) plus granulocyte colony-stimulating factor (G-CSF) compared with etoposide (VP-16) plus pegylated granulocyte colony-stimulating factor (PEG-rhG-CSF) in multiple myeloma (MM) patients. Two hundred forty-four consecutive patients undergoing mobilization with IDCy (3-3.5 g/m 2 ) plus G-CSF (n = 155) were compared with patients receiving VP-16 plus PEG-rhG-CSF (n = 89), including oral etoposide (n = 65) and intravenous etoposide (n = 24). Compared with IDCy, VP-16 use was associated with significantly higher median peak peripheral blood CD34 + cell count (8.20 [range: 1.84-84] × 10 6 /kg vs 4.58 [range: 0.1-27.9] × 10 6 /kg, P   =  .000), and ideal CD34 + cell yield of more than 6 × 10 6 /kg (56.8% vs 35.1%, P   =  .001), notably with a higher efficacy in oral VP-16 use compared with IDCy use (CD 34 + cell counts: median peak peripheral blood 5.87 vs 4.58 × 10 6 /kg and ≥6 × 10 6 /kg [48.4% vs 35.1%]). The median number of apheresis courses was reduced from two in the IDCy group to one in the VP-16 group (P = .000). IDCy use was associated with significantly more frequent episodes of neutropenia (70.2% vs 35.2%; P   =  .000), intravenous antibiotic use (13.2% vs 11.4%; P   =  .672), and hospitalization (P = .000). The recoveries of neutrophils and platelets after autologous stem-cell transplantation were significantly faster in the VP-16 group compared with the IDCy group ( P  = .000). Our data indicate robust stem-cell mobilization in MM patients with VP-16 delivered either orally or intravenously. When compared with intravenous VP-16, oral VP-16 mobilization was associated with significantly more convenient, lower average total costs, and especially decreased the risk of hospital visits and exposure.